Analysis of Classification Technique Algorithms in Data mining- A Review - Nagaparameshwara Chary, S; Rama, B (International Journal of Computer Sciences and Engineering, 2025)
Data mining is the one of the most important research area in the field of Computer Science. By using Data mining techniques we can extract the hidden patterns from large amount of data. The Data mining is the process of categorizing valid, novel, potentially useful and understandable patterns in data. Data mining plays a major role in several application areas like business organizations, Educational institutions, Government sectors, Health care industry, scientific and Engineering. In Data mining techniques classification is one of the most important techniques. The classification technique has several algorithms like ID3,C4.5,Navie Bayes etc. In this paper we analyze the different data mining algorithms. By using these algorithms we can classify our data. Classification is used in every field of real life. The data mining classification technique is used to classify each item in a set of data into one of predefined set of classes or groups. The classification technique is used to predict group membership for data instances. In this Data mining the classification technique include several techniques such as Decision tree, Bayesian classification, Classification by Back propagation, Association Rue mining.